How does intergenerational transmission of the gender-brilliance stereotype take place? Exploring the associations between parents' and children's gender-brilliance stereotypes and parents' stereotypical attributions - Chan, Rachel Sihui (Nanyang Technological University, 2021)
The gender-brilliance stereotype is the belief that males possess higher intellectual ability compared to females. This study examined the intergenerational transmission of the gender- brilliance stereotype by exploring the relationships between parents’ gender-brilliance stereotypes, parents' stereotypical attributions, and children’s gender-brilliance stereotypes. Drawing on previous research on parents’ gender talk and attributions, we created a novel picture book to elicit parents’ stereotypical attributions about the successes and setbacks of a male and female scientist. Parent-child dyads with children aged 7 to 10 participated in the picture book reading session, completed a gender-brilliance Implicit Association Test (Study 1; N = 108) and a measure that explicitly measured the gender-brilliance stereotype (Study 2; N = 21). Parents’ stereotypical attributions made during the reading session were counted and scored using Avitzour et al.’s (2020) coding scheme. Results found that parents and girls endorsed the implicitly measured gender-brilliance stereotype while both parents and children endorsed the explicitly measured gender-brilliance stereotype. Positive associations were found between parents’ and children’s explicitly measured stereotypes, and between parents’ stereotypical attributions and children’s explicitly measured stereotypes but these were not found for implicitly measured stereotypes. Overall, findings suggest that parents’ explicitly measured stereotypes may be a stronger predictor in children’s endorsement of the same stereotype. Our findings also point to the possibility that parents’ stereotypes may be transmitted to their children through their stereotypical attributions.